Impact of COVID-19 lockdown in a biomedical research campus: A gender perspective analysis - Izquierdo-Useros, Nuria; Marin Lopez, Miguel Angel; Monguió-Tortajada, Marta; Muñoz-Moreno, Jose A.; Agusti Benito, Cristina; Morón-López, Sara; Evans, Harvey; Gualdrón-López, Melisa; Müller, Jörg; G Prado, Julia (Frontiers in Psychology, 2022)
From March to September 2020, researchers working at a biomedical scientific campus in Spain faced two lockdowns and various mobility restrictions that affected their social and professional lifestyles. The working group "Women in Science", which acts as an independent observatory of scientific gender inequalities on campus launched an online survey to assess the impact of COVID-19 lockdowns on scientific activity, domestic and caregiving tasks, and psychological status. The survey revealed differences in scientific performance by gender: while male researchers participated in a larger number of scientific activities for career development, female researchers performed more invisible scientific tasks, including peer review or outreach activities. Mental impact was greater in researchers caring for children or dependents, and this was aggravated for women. Results spot a disproportionate impact of COVID-19 lockdowns on female scientific career development, and urges for equity measures to mitigate the consequences of an increase in the gender gap in biomedical sciences.